Crosstalk between arterial components and bioresorbable, 3-D printed poly-l-lactic acid scaffolds. (3rd August 2022) - Wang, Yang; Huang, Yuhua; Du, Ruolin; Ge, Shuang; Li, Yanhong; Wang, Guixue; Wang, Yazhou; Yin, Tieying
Abstract : The accumulation of mechanical changes influences the crosstalk between different vascular characteristics with BRSs behaviors. Elastic arteries are more suitable for the evaluation of BRS degradation and muscular arteries for neointima hyperplasia. Abstract : Bioresorbable scaffolds (BRSs) are designed to provide a temporary support that subsequently leaves behind native vessels after its complete degradation. The accumulation of mechanical changes influences the vascular histological characteristics and vice versa, leading to crosstalk and various behaviors in BRSs in different arterial components, which is different from that observed in traditional metal stents. Hence, we analyzed typical elastic and muscular arteries, the abdominal aorta of Sprague-Dawley rats and carotid arteries of New Zealand rabbits, after both received 3-D printed poly-l -lactic acid BRSs. We observed a lower level of scaffold degradation and severe intimal hyperplasia in the carotid arteries of rabbits because of the synthetic phenotypic transformation of vascular smooth muscle cells (SMCs) and endothelial-to-mesenchymal transition of endothelial cells (ECs). Extracellular matrix remodeling and endothelial repair occurred in a less rapid manner in the abdominal aorta of rats. These results suggest that muscular arterial components such as SMCs and ECs are more sensitive to BRS degradation-induced mechanical changes compared to those of elastic arteries. Therefore, the rat abdominal aorta might be more suitable for assessing BRS degradation and safety, while the carotid artery of rabbits could be used to evaluate drug coatings on BRSs, as it closely reflects the recovery of ECs and proliferation of SMCs. Our study also confirmed that the histological characteristics of vasculature should be considered while choosing an animal model for BRS evaluation.